TINDAK TUTUR EKSPRESIF DALAM PEMBELAJARAN KELAS VIII SMP NEGERI 19 PALU - Azmi, Nurul; Karim, Ali; Zulianto, Zugit (BAHASANTODEA, 2017)
This research aims to describe the use of expressive speech act covering (1) form, (2) function, and (3) strategy in instructional in grade VIII of SMP Negeri 19 Palu. Data source were obtained from teacher and students utterances during the learning process. The approach used the research was pragmatic approach. Method used was descriptive qualitative. Data collections were done in three techniques, namely: (1) recording, (2) observation, and (3) noting. The subjects of the research were teachers and students at SMP Negeri 19 Palu. Technique of analysis was interactive model. The analysis covered four stages, they were: (1) data collection, (2) data reduction, (3) data display, (4) verification/conclusion. The research findings reveal that instructional conducted in SMP Negeri 19 Palu consist of (1) gratitude form, (2) apologize form, (3) thanking form, (4) compliment form, (5) mocking form, (6) blame form, (7) complain form, (8) refuse form, (9) enjoyment form. The function of expressive speech act found in the findings comprised (1) gratitude function, (2) apologize function, (3) thanking function, (4) greeting function. Strategy used in the expressive speech act consists of (1) direct strategy of gratitude, (2) direct strategy of apologize, (3) direct strategy of thanking, (4) direct strategy of compliment, (5) direct strategy of mocking, (6) direct strategy of blame, (7) direct strategy of complain, (8) direct strategy of refuse, (9) direct strategy of enjoyment. Meanwhile the indirect strategy consists of (1) indirect strategy of apologize, (2) indirect strategy of mocking, (3) indirect strategy of complain with variation functions referred to behind the speech act depend on its context.